Social support for youth physical activity: Importance of siblings, parents, friends and school support across a segmented school day - Kolt Gregory S; Schofield Grant; Scragg Robert; Hohepa Maea; Schaaf David (BMC, 2007)
Abstract Background Whilst evidence exists for the influence of encouragement on physical activity participation, the diversity of support sources and the type of physical activity examined previously is limited. This study examined the importance of perceived encouragement from parents, siblings/cousins, friends, and schools on participation levels across three time-specific activity opportunities that are available during a school day (after-school physical activities, lunchtime activity, and active transportation to and from school). Methods A cross-sectional sample of 12-18 year old high school students (n = 3,471) were recruited from low SES schools within South Auckland, New Zealand and categorised as either Junior (Years 9-11) or Senior (Years 12 & 13) students. Participants reported their physical activity levels and quantity of encouragement received from their parent(s), friend(s), sibling(s)/cousin(s), and school to be active. For each physical activity variable participants were dichotomized as being either "active" or "less active". For each social support source, participants were grouped into either receiving "high" or "low" levels of support. Binary logistic regression analyzes were conducted to calculate odd ratios and 95% confidence intervals. Results Low parental support (Juniors, OR: 0.47, 95% CI: 0.38-0.58; Seniors, OR: 0.41, 95% CI: 0.29-0.60) and low peer support (Juniors, OR: 0.61, 95% CI: 0.51-0.74; Seniors, OR: 0.49, 95% CI: 0.35-0.69) were associated with reduced odds of being regularly active after school. For lunchtime activity, low peer support (Juniors, OR: 0.39, 95% CI: 0.32-0.48; Seniors, OR: 0.41, 95% CI: 0.29-0.57) was associated with reduced odds of being categorized as active. While no variables were significantly related to active transportation among senior students, low peer support was associated with reduced odds of actively commuting for Junior students (OR: 0.78, 95% CI: 0.66-0.92). Irrespective of the activity examined, no significant difference was noted for students receiving high support from two parents than students reporting high support from their sole parent in a single parent family. Conclusion The importance of encouragement from parents, siblings, friends, and schools on physical activity is dependant on the time-specific activity examined. It is clear that proximal social networks need to be considered during the development of physical activity promotion strategies.